Raising of the Widow’s Son at Nain (Luke 7:11-17): Exegetical Intertextual Study of Luke-Acts as a Typology of the Elijah-Elisha Narrative - Inyaregh, Abel Aor (Universitas Pelita Harapan, 2025)
The most thoughtful of all the miracles Jesus performed during His earthly ministry are those in which He raised the dead. Liberal theologians, because of natural laws, objected to the logical possibility of miracles. Other folks have disputed the reality of miracles for centuries that they are merely garbage of stories that Jesus’ followers and disciples fabricated. More repeatedly, studies into the literary roots of the New Testament endeavour to connect Jesus' narrative to wonder-workers and holy men from the Greco-Roman world. The raising of a widow's son is unique to the Lukan pericope. This paper attempts to trace an intertextual relationship that exists between Luke-Acts and the Elijah-Elisha narrative. The study adopts narrative and socio-historical criticisms to investigate Luke-Acts as a typology of the Elijah-Elisha narrative, concentrating on the resuscitation of the deceased son of the widow of Nain to validate reality. The study found that the Jesus-Elijah/Elisha typology supports the authenticity and historicity of Jesus raising the dead. The major social issue in the raising of the widow of Nain’s son centres on the vulnerability of a bereaved mother whose only child had died, leaving her without family, social, or monetary upkeep, yet she found solace in Jesus.